Ending the Long-lasting “Difference over the Name” The Prespa Agreement – Its Philosophy, Origins and Challenges Ahead - Sasho Georgievski; Irena Rajchinovska Pandeva (Brill | Schöningh, 2020)
This article offers a broad analysis of the “name issue,” its origins, background and the challenges ahead in light of the Prespa agreement. It posits the historical perspective of both identities, assesses the positions maintained by the parties during the political and diplomatic dispute settlement process and presents the concerns of both parties regarding the agreement. Given the content of the Prespa agreement, the article aims at mapping its essential theoretical frame, explaining the key arrangements in the Prespa agreement and identifying the challenges associated with its implementation that might stand in the way of the accomplishment of its purported “historic” mission of settling the long-lasting disagreements between the two parties, offering some recommendations in that respect.
Keywords: Prespa Agreement; Macedonia; Greece; North Macedonia; name issue; identity